(untitled) (International Seven Journal of Multidisciplinary, 2025)
The country is undergoing changes due to the speed of information and the dissemination of knowledge, forcing organizations to renew their management to efficiently and effectively meet market demands. This process of meeting these new requirements is linked to the pursuit of quality, which is a priority for every company. The quality management system is no longer a competitive differentiator but a system necessary for the survival of organizations, striving for efficiency and customer satisfaction. This paper addresses the application of the PDCA Cycle continuous improvement method in the quality department of a packaging company, identifying losses due to production defects. This study seeks to analyze the reduction of nonconformities generated by poor production in a container machine. Throughout the study, productivity and quality improvement tools will be discussed according to the analyzed stage used by the case study company. Based on the PDCA roadmap, guidelines for reducing nonconformities will be sought. This paper aims to analyze improvement opportunities to reduce nonconformities identified throughout the process to ensure quality delivery and customer satisfaction.